2014
DOI: 10.1007/s11695-014-1330-y
|View full text |Cite
|
Sign up to set email alerts
|

Volume of Resected Stomach as a Predictor of Excess Weight Loss After Sleeve Gastrectomy

Abstract: The VRS can be used as an indicator of excess weight loss 1 year after LSG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…Causey MW et al [ 12 ] reported similar results about the leak pressure generated by the saline solution injection, suggesting the accuracy of this method of measurement with no significant prevalence in the location of the leak. Similar results were obtained by other authors [ 4 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Causey MW et al [ 12 ] reported similar results about the leak pressure generated by the saline solution injection, suggesting the accuracy of this method of measurement with no significant prevalence in the location of the leak. Similar results were obtained by other authors [ 4 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…Significant differences in the results of LSG for RGV>1200 ml were showed in the literature [ 4 , 5 , 13 ]. Other authors have also shown that very high or low RGV cut-off do not determine significant differences between the samples [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to measure RGV, we manually injected saline solution in a 16-Fr Foley catheter inserted in the gastric antrum, until the leakage of the staple line, as found in Litterature. 14,15 We had no difference between…”
Section: Discussionmentioning
confidence: 84%
“…There has been significant interest in the association of the volume of the resected specimen with weight loss. Studies in the past have shown divergent results, with strength of correlation between volume of resected specimen and excess weight loss varying from large 8‐10 to no correlation 11,12 . Current understanding is that the residual gastric volume (RGV) might be a more reliable variable to study, as the volume of the resected stomach might vary significantly with the preoperative stomach volume.…”
Section: Introductionmentioning
confidence: 99%